2021
DOI: 10.1016/j.ijid.2020.10.064
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare worker infections and deaths due to COVID-19: A survey from 37 nations and a call for WHO to post national data on their website

Abstract: Highlights Health-care workers (HCW) are part of the frontline in the struggle against the pandemic. Many HCWs have been infected with the SARS-CoV-2 and have lost their lives worldwide during the pandemic. We performed a survey among members of the ID-IRI and requested the number of HCW deaths and total HCWs infections. Data came from 37 countries and the median of the HCW deaths per 100,000 population of the country was 0.05. Thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
184
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(195 citation statements)
references
References 2 publications
3
184
1
7
Order By: Relevance
“…The number of deaths in Italy was 0.35 per 100,000, second only to Mexico (0.9/100,000) and Azerbaijan (0.44/100,000) (17,18). At present, it has not yet been investigated why the ratio of deaths to total workers regarding Italy is among the highest in the world (17).…”
Section: Covid-19 and Hcws In Italy: The Report By Inailmentioning
confidence: 98%
“…The number of deaths in Italy was 0.35 per 100,000, second only to Mexico (0.9/100,000) and Azerbaijan (0.44/100,000) (17,18). At present, it has not yet been investigated why the ratio of deaths to total workers regarding Italy is among the highest in the world (17).…”
Section: Covid-19 and Hcws In Italy: The Report By Inailmentioning
confidence: 98%
“…They further outlined eight major sources of anxiety during this pandemic on frontline health care professionals. These are (1) difficulty getting the appropriate amount of personal protective equipment, (2) exposed to vulnerable places and fear of contracting the virus, (3) less access to proper testing for COVID-19 and fear of spreading disease to co-workers and family, (4) uncertainty of who will take care of the family if they contract the virus (5) giving time to their wards and spouses amidst lockdown of work and schools, (6) availability of essential commodities for (e.g., food, water, lodging, logistics), (7) being able to be efficient and provide health care if positioned in a new place and (4) lack of updated information.…”
Section: Introductionmentioning
confidence: 99%
“…As expected in a pandemic, health care has been the most heavily affected sector. Not only have health care workers paid a heavy death toll working in close proximity to infected patients [ 3 ], but they have also had to completely transform their activities in order to ensure continuous care for the remaining groups of patients [ 4 ]. We have already shown that the latter has significantly decreased the number of visits in health care facilities among patients with chronic illnesses to receive treatment and appropriate follow-up, or to manage disease or treatment complications [ 5 ].…”
Section: Introductionmentioning
confidence: 99%